Hubungan Antara Profil Trombosit Dengan Hematokrit Pada Pasien Suspek Demam Berdarah Dengue Dan Perbandingan Metode Manual Dan Metode Automatik - Winarti Rahayu; Asnurbaety Dwiyana; Dita Ellyana Artha (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2018)
A research about the correlation between thrombocyte profile and haematocrite on patient suspect dengue hemorrhagic fever (DHF) and the manual and automatic method comparison at Labuang Baji Hospital Makassar has been done. The aim of this research is to compare the test results of thrombocytes and haematocrite on patients. A research observational study with cross sectional approach used blood sample was contained 0.5 ml EDTA and taken from patient which matched the sample criteria. Samples was 32 consist of 13 samples (40.63%) were males and 19 (59.37%) were females. The research result showed that normal thrombocyte was used as an automatic method found on 4 (12.5%) patient and used manual methods found on 6 (18.8%) patients, abnormal thrombocyte results used automatic method found on 26 (81.2% ) patient and used manual method found on 28 (87.5%) patients. While the patient used the method found on 18 (56.3%) patient and used manual methods found on 17 (53.2%) patients, the abnormal hematocrite results used automatic method found on 14 (43.7%) patients and the used manual method found on 15 (46.8%) patients. In the conclusion, there was no decrease in thrombocyte correlation and elevated haematocrite on patient suspect dengue hemorrhagic fever and there was a difference between thrombocyte test results and haematocrite used automatic and manual methods.